Comparative Analysis of Human Tissue Interactomes Reveals Factors Leading to Tissue-Specific Manifestation of Hereditary Diseases - Barshir, Ruth; Shwartz, Omer; Smoly, Ilan Y.; Yeger-Lotem, Esti (PLOS Computational Biology, 2014)
Author Summary An open question in human genetics is what underlies the tissue-specific manifestation of hereditary diseases, which are caused by genomic aberrations that are present in cells across the entire human body. In order to answer this question, we created an extensive resource of protein expression and interactions across 16 main human tissues. Using this resource, we first show that the genes underlying hundreds of hereditary diseases are widely expressed across tissues, yet, enigmatically, cause disease phenotypes in few tissues only. We then identify two distinct, statistically-significant factors that could lead to tissue-specific vulnerability in the face of this broad expression: (i) many disease-causing genes have elevated expression levels in their disease tissues, and (ii) disease-causing genes have a significantly higher tendency for tissue-specific interactions in their disease tissues. As we show for several disease-causing genes, these tissue-specific interactions highlight disease mechanisms and provide an efficient filter for interrogating the molecular basis of diseases. Together the two factors we identified are relevant for as many as two thirds of the tissue-specific hereditary diseases. Our comparative tissue analysis therefore provides a meaningful and efficient framework for enhancing the understanding of the molecular basis of hereditary diseases.